Cyberterrorism: A Survey of Researchers - Stuart Macdonald (2013)
This report provides an overview of findings from a project designed to capture current understandings of cyberterrorism within the research community. The project ran between June and November 2012, and employed a questionnaire which was distributed to over 600 researchers, authors and other experts. Potential respondents were identified using a combination of methods, including targeted literature reviews, standing within relevant academic communities, snowballing from earlier participants or contacts, and the use of two mailing lists. 118 responses were received in total, from individuals working in 24 countries across six continents